Studi Stabilitas Tanah Ekspansif dengan Penambahan Pasir untuk Tanah Dasar Konstruksi Jalan - Sutikno Sutikno; Denny Yatmadi (Politeknik Negeri Jakarta, 2010)
Abstract Problems of ekspansive soil is stability (CBR) and swelling effect of process of compaction. One of the soil expansive component in general is sand beside silt and clay, added sand will make composition of clay to downhill expansive soil. With condensation process conducted by mixing of sand to ekspansive soil with addition composition equal to 10%, 20%, 30%. and 35% to dry weight of ekspansive soil. Conclusion which in earning: Level of CBR mount above ekspansive soil of genuiness come up with the condition of addition of sand counted 30% to the condition of soaked, while at addition of sand up to 35%, value of CBR (downhill stabilitation) but still above original ekspansive soil value, at addition of sand up to 35%, value of CBR (downhill stabilitation) but still above original ekspansive soil value. For the development of (ekspansive soil swelling) of ekspansive soil with addition of sand, condition of natural swelling of value and reduction isn't at addition of sand between 10 to 30% and lower at addition of sand counted 35%. There are influence of addition of sand at ekspansive soil compacted to stability (CBR) and swelling of ekspansive natural of change which are positive after mixed with sand, tired optimasi at addition of sand between 20% up to 30%. Keyword : ekspansif soil, sand, condensation, stability